2012
DOI: 10.1182/blood-2011-06-363655
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-dependent anti-cytomegalovirus activity of human γδ T cells expressing CD16 (FcγRIIIa)

Abstract: Human cytomegalovirus (HCMV) infection is an important cause of morbidity and mortality in transplant recipients. Long-term protective immunity against HCMV requires both sustained specific T-cell response and neutralizing IgG production, but the interplay between these effector arms remains poorly defined. We previously demonstrated that ␥␦ T cells play a substantial role as anti-HCMV Tcell effectors. The observation that CD16 (Fc␥RIIIA) was specifically expressed by the majority of HCMV-induced ␥␦ T cells pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 44 publications
6
119
0
1
Order By: Relevance
“…In close resemblance, HCMVinduced gd T cells secrete IFN-g in response to IgG-opsonized virions (35). We previously reported that NK cells may directly sense HCMV through a TLR2-dependent mechanism (55).…”
Section: Nk Cells As Sensors For Viral Particle-ab Immune Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…In close resemblance, HCMVinduced gd T cells secrete IFN-g in response to IgG-opsonized virions (35). We previously reported that NK cells may directly sense HCMV through a TLR2-dependent mechanism (55).…”
Section: Nk Cells As Sensors For Viral Particle-ab Immune Complexesmentioning
confidence: 99%
“…CD16 + gd T cells have been shown to produce IFN-g when incubated with IgG-opsonized HCMV virions (35). We assessed whether NKG2C bright NK cells could also respond to viral particles in the presence of specific IgG.…”
Section: Nkg2c Bright Nk Cells Recognize Ab-cmv Immunocomplexesmentioning
confidence: 99%
“…In liver transplantation, cd T cell genes were included in the gene expression signature of tolerant recipients (195), and intragraft cd T cell infiltration was associated with pediatric liver transplant tolerance (196). cd T cells have also been linked to allograft rejection by observations suggesting that cd T cells expressing the Fc-c receptor CD16 bind donor-specific antibodies and participate in allograft injury via ADCC (197). CMV-infected and immunized patients have increased numbers of cd T cells and higher levels of donor-specific antibodies (198).…”
Section: Innate Immune Pathways In CMV Infectionmentioning
confidence: 99%
“…Alternatively, gd T cell lines also were used to study the cytotoxic response of Vg9Vd2 T cells to HSV-1 (17) to document noncytolytic antiviral activity and IFN-g production against severe acute respiratory syndrome virus (14), as well as Fas-Fas ligand-and perforin-granzyme B-dependent cytotoxicity against cells infected with influenza A virus (18). T cell lines also were used to study the IFN-g response of Vd2 2 gd T cells to fibroblasts infected with CMV (19). It was reported that the activation marker CD69 is upregulated on gd T cells during dengue infection (20).…”
mentioning
confidence: 99%